FORMULASI GRANUL EFFERVESCENT DARI LIOFILISAT MAHKOTA BUNGA KASUMBA TURATE (Carthamus tinctorius Linn) SEBAGAI SUPLEMEN ANTIOKSIDAN ALAMI - Diana Astuti; Yulfira Amalika; Mochammad Hamzah Haz (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2019)
Infection is the highest prevalence of disease in Indonesia. Efforts to increase the prevalence of infection is to improve the community's immune system. Kasumba turate is an endemic plant of South Sulawesi empirically used in the cure of smallpox and improve the nature of the body due to the nature of its imunomodulator. Traditional decoction of the Kasumba turate is less effective for consuming because it has a bitter taste, so the aim of this study is to modified decocta of kasumba turate becomes effervescent granules which is contain antioxidant to reducing free radicals in the body without reduce its usefulness. The method of making effervescent granule supplementation is by using infusa (decoction) from a lyophilized kasumba flower with Freeze Dryer and formulated with a combination of citric acid and sodium bicarbonate 1: 1.5. Effervescent granule preparationss were evaluated by LOD, MC, compressibility, species weight and pH test to obtain a qualified preparation and antioxidant analysis by DPPH method. Based on the evaluation of the preparation, it is found that the effervescent kasumba turate granule fulfill the applicable requirements: acid granules obtained% MC and% LOD 0.5% and 0.5%, basic granule% MC and% LOD 0.7%, 0.77%, flow properties break 27o, and flow rate 9.7 g/s),% compressibility 16% and weight type 1.66, pH of the preparation 7. The effervescent lyophilisate preparation of kasumba turate becomes an effective supplement in enhancing the immune system and as an antioxidant for all age.